West view of the interior of St. Paul's, Shadwell, taken down 1817 - Dale; Schnebbelie, Robert Blemmell (Tufts Archival Research Center, 2008)
Looking toward the altar. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.